2021
DOI: 10.1093/ofid/ofab660
|View full text |Cite
|
Sign up to set email alerts
|

Model-Based Efficacy and Toxicity Comparisons of Moxifloxacin for Multidrug-Resistant Tuberculosis

Abstract: Background Moxifloxacin (MOX) is used as a first-choice drug to treat multi-drug-resistant tuberculosis (MDR-TB), however, evidence-based dosing optimization should be strengthened by integrative analysis. The primary goal of this study was to evaluate MOX efficacy and toxicity using integratvie model-based approaches in MDR-TB patients. Methods In total, 113 MDR-TB patients from five different clinical trials were analyzed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…29 We also demonstrated that the LXF MXF and LFX data for MDR-TB patients have been described by a one-compartment model in some previous studies 30,31 and by a two-compartment model in others. 32,33 The reason for this variation is unclear. The differences in the total sample size and number of plasma samples collected during the elimination phases in the studies could be a reason for the observed variations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 We also demonstrated that the LXF MXF and LFX data for MDR-TB patients have been described by a one-compartment model in some previous studies 30,31 and by a two-compartment model in others. 32,33 The reason for this variation is unclear. The differences in the total sample size and number of plasma samples collected during the elimination phases in the studies could be a reason for the observed variations.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the appeal of a higher starting dose of MXF for optimizing outcomes, our findings may explain a study in Indian MDR-TB patients in a tertiary care center in Mumbai, which found that an increased MXF dosing did not improve treatment outcomes in the presence of low-level resistance to MXF. 38 More interestingly, another recent study by Yun et al 32 suggested a twice 400 mg instead of a single 800 mg MXF is an optimal dosing regimen for MDR-TB patients because it provides superior efficacy and safety. BMI was shown to have a statistically significant influence on V for MXF.…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of studies have focused on balancing the efficacy and toxicity of MDR-TB, but no breakthroughs have been made (Bigelow, Tasneen, Chang, Dooley, & Nuermberger, 2020;Yun et al, 2022). We collected primary data from 12 patients with MDR-TB, including gender, age, dose, duration of treatment, presence of peripheral nerve discomfort, self-assessment of pain, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Levofloxacin was chosen as a versatile antibiotic that works on both Gram-positive and Gram-negative bacteria [26] . A key medication for treating a variety of diseases is the respiratory quinolone moxifloxacin (MOX), particularly for the treatment of tuberculosis and pneumonia [27] , [28] .…”
Section: Introductionmentioning
confidence: 99%